Correlations Between Pre- and Post-Fasting Growth in Nile Tilapia - Barreto, Rodrigo Egydio [UNESP]; de Miranda Cabral Gontijo, Alisson Marques; Delicio, Helton Carlos [UNESP] (Garuda Scientific Publications, 2008)
We tested the correlation between growth rate before and after a food deprivation phase in twelve single held Nile tilapias, Oreochromis niloticus. The experiment was divided into three phases: before food deprivation (phase 1: 15 d), food deprivation (phase 2: 12 d) and refeeding (phase 3: 15 d). The specific growth rate - SGR, food conversion efficiency - FCE and feed ingestion increased significantly during phase 3. Positive and significant correlations were found either to SGR or to feed ingestion between Phase 1 and 3 but not for FCE. The SGR on phase 3, moreover, were positively correlated to FCE and feed ingestion, while on phase 1 SGR was positively correlated to FCE only. Thus, high pre-fasting SGR or feed ingestion reflects in likewise high post-fasting SGR or feed ingestion values. Moreover, since SGR and FCE are correlated to each other in both phase 1 and 3, but phase 3 SGR is also correlated to feed ingestion; we could suppose that hyperphagic behaviour could be the main compensatory mechanism. Accordingly, we suggest that a fish with an elevated growth performance shall display a proportionally raised post-fasting growth response in order to normalize its predetermined growth trajectory and resume its normal growth rate.
Keywords: Growth; food deprivation; fish; Nile tilapia; Oreochromis niloticus